Transmission expansion planning and long term marginal prices calculation using simulated annealing - João Paulo Tomé Saraiva (2003)
This paper addresses the problem of transmission expansion-planning in the context of the re-regulation and liberalization of power systems. The transmission expansion-planning problem is formulated as an integer problem and it is solved keeping that characteristic using Simulated Annealing. In the scope of the access to the transmission networks and the corresponding payments for Use of Networks, the paper discusses the advantages and drawbacks from adopting several cost methods and, more specifically, short-term and long-term nodal marginal prices. Long-term marginal prices are computed in the framework of the Simulated Annealing algorithm and led to the calculation of the Marginal Based Remuneration to the transmission company. The paper includes case studies based on the Portuguese 400/220/150 kV network and on a didactic 6-bus system.